Lexicology and its Main Functions - Mullabayeva Lola Shaniyazovna (Zien Journals, 2022)
This article describes in detail the main tasks of lexicology, general issues of lexicology of lexicology of all languages, collection and systematization of terms used in the Uzbek language, the main issues of lexicology, the laws of practical use and development of lexicology.
Keywords: lexicology; thematic group; fixed compounds; general lexicology and private lexicology